SIRT1 activator isolated from artificial gastric juice incubate of total saponins in stems and leaves of Panax ginseng. Issue 3 (1st February 2018) - Yang, Xiu-Wei; Ma, Li-Yuan; Zhou, Qi-Le; Xu, Wei; Zhang, You-Bo
Graphical abstract: Highlights: Two new dammarane-type triterpenoids (1 and 2 ) were isolated. Structures of the new dammarane triterpenoids were elucidated by spectroscopic analysis. Compounds 11, 17, 18, 20, 23, 24, 28, and 29 were the potential activator of SIRT1. Results were helpful to explain the longevity effect of ginseng from the new field of view. Abstract: Panax ginseng as a traditional Chinese medicine has been extensively used for the treatment of many diseases, especially in prolonging life and anti-tumor. Dammarane-type triterpenoids from P. ginseng have diverse beneficial effects and their chemical structures can be modified in the gastrointestinal tract after oral administration. In this paper, the dammarane-type triterpenoids were isolated from artificial gastric juice incubate of total saponins in the stems and leaves of P. ginseng through column chromatographic methods and their chemical structures were determined based on spectral data. Two new dammarane-type triterpenoids named ginsenotransmetins B (1 ) and C (2 ), along with twenty-nine known compounds (3 –31 ), were obtained. All 31 compounds isolated were investigated for their activities of SIRT1 using SIRT1 fluorometric drug discovery assay kit. Among them, compounds 11, 17, 18, 20, 23, 24, 28, and 29, which were found to be potential as SIRT1 activators, exhibited significant stimulation of SIRT1 activity. The results showed that these compounds may be considered to be a useful medicinal resource for prolonging life and anti-tumor. In addition, the results were helpful to explain the longevity effect of ginseng from the new field of view.